2014
DOI: 10.1007/s00264-014-2525-5
|View full text |Cite
|
Sign up to set email alerts
|

Vertebroplasty versus kyphoplasty in osteoporotic vertebral compression fracture: a meta-analysis of prospective comparative studies

Abstract: Based on current evidence, PVP takes less time in the operation, while it has greater risk of cement leakage, was inferior in reducing Cobb angle in the long term and results in lower anterior vertebral body height after the surgery. For pain relief, which is the main desire of the patients, both procedures provide significant improvement in VAS and ODI pain scores. PVP is still an effective procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 36 publications
3
47
1
1
Order By: Relevance
“…Studies by Yan et al (24,14) reported that pain and the kyphotic angle were reduced in their unilateral and bilateral groups, whereas the volume of the injected cement and radiation dose in the unilateral group were lower than those in the bilateral group. Hence, the current study demonstrated that unilateral PKP had a similar curative effect as bilateral PKP, and the radiation dose, operative time and complication rate were all lower than those in the bilateral PKP group, which was consistent with the results of previous studies (13) In the unilateral puncture approach, the inclined angle of the puncture is increased to distribute the bone cement to the opposite side, which increases puncture-associated risks. To address these issues, the balloon must be placed in the anterior one-third of the vertebral body to allow the bone cement to diffuse into the midline and contralateral vertebral body (25).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies by Yan et al (24,14) reported that pain and the kyphotic angle were reduced in their unilateral and bilateral groups, whereas the volume of the injected cement and radiation dose in the unilateral group were lower than those in the bilateral group. Hence, the current study demonstrated that unilateral PKP had a similar curative effect as bilateral PKP, and the radiation dose, operative time and complication rate were all lower than those in the bilateral PKP group, which was consistent with the results of previous studies (13) In the unilateral puncture approach, the inclined angle of the puncture is increased to distribute the bone cement to the opposite side, which increases puncture-associated risks. To address these issues, the balloon must be placed in the anterior one-third of the vertebral body to allow the bone cement to diffuse into the midline and contralateral vertebral body (25).…”
Section: Discussionsupporting
confidence: 90%
“…Frontal and lateral chest X-ray, computed tomography in cases of injured vertebrae and chest magnetic resonance imaging were performed prior to surgery. There were no significant inter-group differences in terms of sex, age, course of disease, lesional segment, bone density T-value, pre-operative visual analog scale (VAS) pain score, Oswestry disability index (ODI), vertebral body height and Cobb angle (13) (Table I).…”
Section: Patientsmentioning
confidence: 99%
“…In a meta-analysis of prospective comparative studies of vertebroplasty and kyphoplasty, Chang et al 27 included 1429 patients from 20 studies and found that there was no difference in the reduction of pain and disability between the two techniques. Similar findings were reported in another meta-analysis of 845 patients 28.…”
Section: Resultsmentioning
confidence: 99%
“…The emerging increase in kyphoplasty procedures may be the result of a majority of procedures performed by radiologists since 2012 (22). (24).…”
Section: Discussionmentioning
confidence: 99%